2016
DOI: 10.3390/ma9060467
|View full text |Cite
|
Sign up to set email alerts
|

The Repetitive Detection of Toluene with Bioluminescence Bioreporter Pseudomonas putida TVA8 Encapsulated in Silica Hydrogel on an Optical Fiber

Abstract: Living cells of the lux-based bioluminescent bioreporter Pseudomonas putida TVA8 were encapsulated in a silica hydrogel attached to the distal wider end of a tapered quartz fiber. Bioluminescence of immobilized cells was induced with toluene at high (26.5 mg/L) and low (5.3 mg/L) concentrations. Initial bioluminescence maxima were achieved after >12 h. One week after immobilization, a biofilm-like layer of cells had formed on the surface of the silica gel. This resulted in shorter response times and more inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The results demonstrated that luminescence was stable and the highest at 2-2.5 h after incubation for T3-lux-E. coli and T7-lux-E. coli or 1-1.5 h after incubation for SP6-lux-E. coli. The time was equal to or shorter than that previously reported for the lux-based bioluminescent bioreporter P. putida TVA8 (2 h) and luminescence bacterial biosensors without the T7 promoter (3 h) for toluene measurement [6,21]. Therefore, on average, 20-min consecutive measurements were recorded when T3-lux-E. coli and T7-lux-E. coli were cultured for 2 h and when SP6-lux-E. coli was cultured for 1 h. The maximum average luminescence induced by 200 μM toluene for T3-lux-E. coli, SP6-lux-E. coli, and T7-lux-E. coli was 1020 ± 17.6, 510 ± 14.1, and 2120 ± 63.8 RLU, respectively.…”
Section: Resultsmentioning
confidence: 63%
“…The results demonstrated that luminescence was stable and the highest at 2-2.5 h after incubation for T3-lux-E. coli and T7-lux-E. coli or 1-1.5 h after incubation for SP6-lux-E. coli. The time was equal to or shorter than that previously reported for the lux-based bioluminescent bioreporter P. putida TVA8 (2 h) and luminescence bacterial biosensors without the T7 promoter (3 h) for toluene measurement [6,21]. Therefore, on average, 20-min consecutive measurements were recorded when T3-lux-E. coli and T7-lux-E. coli were cultured for 2 h and when SP6-lux-E. coli was cultured for 1 h. The maximum average luminescence induced by 200 μM toluene for T3-lux-E. coli, SP6-lux-E. coli, and T7-lux-E. coli was 1020 ± 17.6, 510 ± 14.1, and 2120 ± 63.8 RLU, respectively.…”
Section: Resultsmentioning
confidence: 63%
“…The results demonstrated that luminescence was stable and the highest at 2-2.5 h after incubation for T3-lux-E. coli and T7-lux-E. coli or 1-1.5 h after incubation for SP6-lux-E. coli. The time was equal to or shorter than that previously reported for the lux-based bioluminescent bioreporter P. putida TVA8 (2 h) and luminescence bacterial biosensors without the T7 promoter (3 h) for toluene measurement [6,21]. Therefore, on average, 20-min consecutive measurements were recorded when T3-lux-E. coli and T7-lux-E. coli were cultured for 2 h and when SP6-lux-E. coli was cultured for 1 h. The maximum average luminescence induced by 200 μM toluene for T3-lux-E. coli, SP6-lux-E. coli, and T7-lux-E.…”
Section: Sp6 T3mentioning
confidence: 63%
“…Conventional analytical techniques, such as gas chromatography (GC) and high-performance liquid chromatography, are sensitive and reliable for toluene detection but are time-consuming, expensive, and laboratory-bound, and they require large equipment and specialized training [5,6]. By contrast, biological methods can be useful alternatives for organics detection because they are low cost, easy to use, portable, small, and highly specific and can detect bioavailability [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Genetically modified organisms have also been coupled to optical fibers for the development of label-free biosensors for the sensitive and selective detection of a wide range of compounds of interest in different fields such as food analysis, environmental monitoring, and clinical diagnostics, among others [49,50,51,52,53]. Sensor performance depends on the introduction of a reporter gene into the host cell, whose expression is modulated by the interaction of the analyte with the molecular recognition element, and promoter sequences [54].…”
Section: Fiber Optic and Evanescent Wave Biosensorsmentioning
confidence: 99%
“…A robust biomolecule coating on the sensor surface should be stable and, in many cases, preferably regenerable. It is critical to ensure that the surface coating and the immobilization do not degrade the biological activity of the recognition element or result in steric hindrance, and a sufficient number of molecules must be immobilized to ensure reliable signals simultaneously minimizing the non-specific binding to the surface [50]. The following sections discuss SPR-based methods reported for small molecule detection using different recognition elements, and Table 1 summarizes some of the most interesting approaches from recent years.…”
Section: Surface Plasmon Resonancementioning
confidence: 99%